Imaging specific cellular glycan structures using glycosyltransferases via click chemistry. (22nd December 2017) - Wu, Zhengliang L; Person, Anthony D; Anderson, Matthew; Burroughs, Barbara; Tatge, Timothy; Khatri, Kshitij; Zou, Yonglong; Wang, Lianchun; Geders, Todd; Zaia, Joseph; Sackstein, Robert
Abstract: Heparan sulfate (HS) is a polysaccharide fundamentally important for biologically activities. T/Tn antigens are universal carbohydrate cancer markers. Here, we report the specific imaging of these carbohydrates using a mesenchymal stem cell line and human umbilical vein endothelial cells (HUVEC). The staining specificities were demonstrated by comparing imaging of different glycans and validated by either removal of target glycans, which results in loss of signal, or installation of target glycans, which results in gain of signal. As controls, representative key glycans including O-GlcNAc, lactosaminyl glycans and hyaluronan were also imaged. HS staining revealed novel architectural features of the extracellular matrix (ECM) of HUVEC cells. Results from T/Tn antigen staining suggest that O-GalNAcylation is a rate-limiting step for O-glycan synthesis. Overall, these highly specific approaches for HS and T/Tn antigen imaging should greatly facilitate the detection and functional characterization of these biologically important glycans.